Recent CMV Research (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
I am very pleased with this Viruses Special Issue. Of particular interest to families and caregivers affected by CMV diseases are several papers: addressing prevention of CMV infection of trophoblast cells (Zydek et al., 2014), CMV latency (Sinclair and Reeves, 2013), as well as of CMV lung infections in non-HIV infected children (Restrepo-Gualteros et al., 2014). Our ability to enhance immune responses for controlling CMV infection (Hanley and Bollard, 2014) and new strategies for CMV vaccine development guided by non-human primate studies (Deere and Barry, 2014) are discussed in two excellent reviews. Several articles address the CMV manipulation of the immune system, both innate and adaptive immune responses (Stevenson et al., 2014, Fink et al, 2013, 2014, Raghavan et al., 2014) and of DNA damage responses (E and Kowalik, 2014; Kulkarni and Fortunato, 2014). [...]